Assessment of water quality in the AIT campus peripheral canal system - Khairzada, Masoda; Shipin, Oleg V.; Annachhatre, Ajit P.; Nguyen, Thi Kim Oanh; Asian Institute of Technology; Ministry of Higher Education (MoHE), Afghanistan Partnership Project (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Wetlands have value because their functions have proved to be useful to humans. The unit value for some wetlands also increases with human development (agriculture and urban) because of increased use and/or increased scarcity. The study was undertaken at AIT peripheral canal system with the view to monitor surface water quality. Surface water samples were collected from AIT peripheral canal system (6 stations) over a 4 month period and analyzed with the aim to evaluate their use as potential indicators of pollution. Surface water quality is being deteriorated by nutrient input caused by the sewage leakage. The field study assesses that total macrophyte coverage was 5-7% with Salvinia sp. Estimation of pollution level at AIT peripheral canal showed mean COD 81mg/L, E. coli concentration 3.6-36 MPN/100mL, chlorophyll a concentration 51-382 og/L and turbidity was 2.8-50 NTU, where dominated algal species was Euglena sp. The E. coli presence indicated wastewater seepage, which was the prominent source of pollution. The presence or absence of aquatic macrophytes is one of the characteristics used to define wetlands, and as such macrophytes are an indispensable component of these ecosystems. As the most important removal processes in constructed treatment wetlands are based on physical and microbial processes, the role of the macrophytes in these has been questioned. This paper summarizes how macrophytes influence the treatment processes in wetlands. The effect of emergent macrophyte (Nymphaea) studied in 0.250 mp3 (Bwetlands. Result showed that there is direct effect of emergent macrophyte (Nymphaea) on chlorophyll a concentration, turbidity, evapotranspiration and algal species. Under 80 % coverage, chlorophyll a concentration didn{u2019}t increase and approached to zero in 32 days (as initial concentration was 97.6 og/L) where turbidity and evapotranspiration values were low as compare to 0 and 40 % coverage. On the other hand, chlorophyll a value increase with slow rate (3.83og/L/day) and provide a diverse algal system under 40% coverage. Evapotranspiration rate for 0% coverage was 2.1mm/day more than 80% coverage and 1.5mm/day as compare to 0 % coverage.s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2015
Keywords: Water quality -- Evaluation -- Asian Institute of Technology (Thailand)